THE EFFECT OF DEFERRED TAX ASSETS, CURRENT TAX EXPENSES AND LEVERAGE ON PROFIT MANAGEMENT - Diana Fajarwati; Nurlaila Maysaroh C; Annafi Indra Tama; Indrawan Eko Putranto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this research is to measure and determine whether Deferred Tax Assets, Current Tax Expenses, and Leverage have an effect on Earning Management. Research objects in manufacturing companies listed on the Indonesia Stock Exchange (IDX) 2016 - 2018. The research method uses quantitative research and purposive sampling data collection techniques according to the criteria, a sample of 74 observational data for three years. The researcher analyzed the data using Multiple Regression, using an analysis tool in the form of SPSS. From the discussion, it is found that (1) deferred tax assets have no positive effect on earnings management, (2) current tax expense has no positive effect on earnings management, and (3) Leverage has no positive effect on earnings management.